Assessment of Different Epitaxial Transfer Techniques for High Frequency III-V Devices - Tavakoli Dastjerdi, M. Hadi (My University, 2010)
The main aim of this work is to transfer the epitaxially grown, indium phosphide based material structure of heterostructure barrier varactor onto silicon substrate. However, these techniques can be also employed for other high frequency and optoelectronics devices such as laser diodes -hybird lasers-, transistors, photodetectors and photonics interconnects. Different wafer bonding techniques were explored and compared. Test diodes were fabricated on the bonded samples and electrical measurements (I-V and CV) were compared to the results with the reference samples on the original indium phosphide substrate. These measurements verified the quality of epitaxial transfer. Also in order to adapt the remaining processing steps to the initial wafer bonding, a study of ohmic contacts was performed to measure the specific contact resistances for alloyed and non-alloyed ohmic contacts.
Keywords: Elektroteknik och elektronik; Electrical Engineering, Electronic Engineering, Information Engineering